Peran Guru dalam Pembentukan Karakter Kewirausahaan pada Pembelajaran Tatap Muka Terbatas Mata Pelajaran Produk Kreatif dan Kewirausahaan Kelas XI SMKN 2 Boyolangu - Erna Sulistiyan; Nanis Hairunisya; Imam Suwaktus Suja’i (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
The purpose of this review is to determine the teacher's role in the planning, implementation, evaluation process of entrepreneurial character formation in limited face-to-face learning in the subjects of Creative Products and Entrepreneurship class XI SMKN 2 Boyolangu. The literature is the role of the teacher, character education, entrepreneurial character, limited face-to-face learning. This research is qualitative with a case study method approach. The research was conducted by examining the current condition of the implementation of learning at SMK Negeri 2 Boyolangu. This research includes the pre-field stage, field work stage, and data analysis stage. Data analysis used data analysis according to J. P. Spradley. The research subjects in this study were teachers of Class XI Creative Products and Entrepreneurship (PKK) at SMKN 2 Boyolangu. Data collection techniques were carried out through observation, interviews and documentation methods. Based on the results of the study that the teacher's role in planning is as a planner of learning activities. The teacher's role in implementation is: as an educator (educating students), as a manager (class manager) - teaching according to KD, as an actor (implementing learning). The teacher's role in evaluating the formation of entrepreneurial character is as a supervisor and motivator, as an integrator - evaluating learning through PKG and strengthening character